Sustained release of Sr and Ca from a micronanotopographic titanium surface improves osteoblast function - Faria, Luan Viana [UNESP]; Lopes, Maria Eduarda Scordamaia [UNESP]; de Oliveira, Diego Pedreira; da Silva, Fernando Santos; Fugivara, Cecilio Sadao [UNESP]; Nogueira, Andressa Vilas Boas; Deschner, James; Cirelli, Joni Augusto [UNESP] (Springer Nature, 2025)
The surface chemistry and topographical features of dental implants play a crucial role in influencing the osseointegration process. Alkaline earth elements such as strontium (Sr) and calcium (Ca) exert beneficial effects in promoting bone formation. This study aimed to evaluate micronanotopographic cpTi substrates that doped these elements, Sr and Ca. The composition and morphology were analyzed by X-ray photoelectron spectroscopy, scanning electron microscopy (SEM), and atomic force microscopy (AFM). Wettability assays, Sr and Ca release tests, and electrochemical behavior were also conducted. Proliferation, adhesion, and differentiation of MC3T3-E1 cells on this surface were evaluated in vitro. Direct fluorescence assays and SEM, cell viability, alkaline phosphatase (ALP) activity, and mineralization nodule formation were performed. The biological results showed the absence of cytotoxicity after the treatments, increased cell spreading on the micronanotopographic substrates, and greater mineralization nodule formation on surfaces doped with Sr and Sr/Ca. Gene and protein expression of osteoblastic markers were assessed through PCR and ELISA, and some genes were regulated on the doped surfaces at three and seven days of cell culture, like Bglap, Ibsp, Spp, Col1a1, and Runx2. The micronanotopographic substrates modified the physicochemical properties and morphology of the pre-osteoblasts. The results indicate that the biological effect of implants treated with Sr and Sr/Ca was significantly superior to that of polished surfaces and undoped micronanotopographic implants. Furthermore, the addition of Sr alone was sufficient to improve events related to osseointegration.
Keywords: Calcium; Dental implants; Osteogenesis; Strontium